Impact pressures generated by spherical particle hypervelocity impact on yorkshire sandstone - Miljković, K.; Taylor, E.A.; Tsembelis, K.; Proud, W.G.; Cockell, C.S.; Zarnecki, J.C. (AMER INST PHYSICS, 2007)
Hypervelocity impact tests were carried out at 4.8 km/s using the Open University's All Axis Light Gas Gun (AALGG) in the Planetary and Space Sciences Research Institute (PSSRI)'s Hypervelocity Impact Laboratory. A first estimate of the peak loading pressures was made using preliminary hydrocode simulations, supported by calculations. Following a review of existing published quartz and sandstone data, our previously published plate impact data were combined with high pressure quartz data to produce a synthetic Hugoniot. This will form the basis of future hydrocode modelling, as a linear Us-Up relationship does not adequately represent the behaviour of sandstone over the pressure range of interest, as indicated by experimental data on Coconino sandstone. This work is a precursor to investigating the biological effects of shock on microorganisms in sandstone targets. This paper also contains the first presentation of results of ultra high speed imaging of hypervelocity impact at the Open University. © 2007 American Institute of Physics.